Attraction of the private sector into the port industry of Kazakhstan - Manasbay А.Е. (BUKETOV BUSINESS REVIEW, 2019)
This article is aimed at identifying the most appropriate forms of private sector involvement in the provision of Aktau port services considering the type of the services being offered. To achieve this goal, the following methods have been used: traditional forms of private sector participation in the organization of port services were considered, existing forms of private sector participation in the organization of Aktau port services were identified and ownership forms for Aktau port assets and services were identified. Based on the descriptive, comparative and content analysis the following conclusions have been made. First, reforms in the global port industry are characterized primarily by the use of concession contracts involving private sector participation, and not the sale of seaport assets to the private sector. Second, the following forms of private sector participation in the port industry of port Aktau are used: creation of joint ventures, trust management and transfer of part of the port to a private owner. Third, the private and public sectors coexist: both the public and private sectors own the main assets of the port, respectively, provide port services through the use of these assets. Fourth, at the present stage of development, the most optimal is the transfer of assets of the port of Aktau (oil, ferry and grain terminal) to the private party for a long-term lease under the conditions of minimum turnover / minimum rental payment. It is proposed to transfer dry cargo berths to the private sector on a concession basis. Fifth, legislative restriction on the prohibition of the sale of sea terminals within the framework of the concession is a significant restriction for further building an effective operating management model and changing relations with private stevedoring companies.